Vulnerability variables among octogenerian myeloma patients: a single-center analysis of 110 patients. Issue 3 (23rd February 2019) - Gavriatopoulou, Maria; Fotiou, Despina; Koloventzou, Ursula; Roussou, Maria; Migkou, Magdalini; Ntanasis-Stathopoulos, Ioannis; Kanellias, Nikolaos; Ziogas, Dimitrios C.; Panagiotidis, Ioannis; Gika, Dimitra; Eleutherakis-Papaiakovou, Evangelos; Terpos, Evangelos; et al.
Abstract: In the era of an aging population, an increasing number of patients are diagnosed with multiple myeloma at an age of ≥80. The frailty of this population as a result of coexisting comorbidities and age-related organ impairment is a significant management challenge. The aim of our study was to analyze the disease characteristics, frailty scores and toxicity profile in relation to patient outcomes. Among 827 consecutive, newly diagnosed, symptomatic patients treated since 01 January 2000, we analyzed the characteristics and outcomes of the 110 who were ≥80. Median survival was 21 months, and early mortality within 2 months from diagnosis was 20%. Several factors were associated with inferior survival, whereas in the multivariate analysis, estimated glomerular filtration rate (eGFR) < 30 ml/min/1.73m 2 and LDH ≥250 IU/L were independently associated with poor overall survival. These patients are a distinct frail subset of the general myeloma population who require individualized approach.